Intraductal carcinoma of prostate reporting practice: a survey of expert European uropathologists. Issue 10 (29th February 2016) - Varma, Murali; Egevad, Lars; Algaba, Ferran; Berney, Daniel; Bubendorf, Lukas; Camparo, Philippe; Comperat, Eva; Erbersdobler, Andreas; Griffiths, David; Grobholz, Rainer; Haitel, Andrea; Hulsbergen-van de Kaa, Christina; et al.
Abstract : Background: It is unclear whether the reported variation in the diagnosis of intraductal carcinoma of the prostate (IDC-P) is due to variable interpretation of borderline morphology, use of different diagnostic criteria or both. Aims: We sought to determine the degree of variation in the diagnostic criteria and reporting rules for IDC-P in prostate biopsies employed by expert uropathologists. Methods: A questionnaire survey was circulated to 23 expert uropathologists from 11 European countries. Results: Criteria used for diagnosis of IDC-P included solid intraductal growth (100%), dense cribriform (96%), loose cribriform/micropapillary with nuclear size >6× normal (83%) or comedonecrosis (74%) and dilated ducts >2× normal (39%). 'Nuclear size' was interpreted as nuclear area by 74% and nuclear diameter by 21%. Pure IDC-P in needle biopsies was reported by 100% and Gleason graded by 30%. All would perform immunohistochemistry in such cases to rule out invasive cancer. An IDC-P component associated with invasive cancer would be included in the determination of tumour extent and number of cores involved by 74% and 83%, respectively. 52% would include IDC-P component when grading invasive cancer. 48% would perform immunohistochemistry in solid or cribriform nests with comedonecrosis to exclude IDC-P (17% routinely, 30% if the focus appeared to have basal cells on H&E). 48% graded such foci as Gleason pattern 5 even if immunohistochemistry demonstrated the presence of basal cells. Conclusions: There is a need for more clarity in the definition of some of the diagnostic criteria for IDC-P as well as for greater standardisation of IDC-P reporting.